2006
DOI: 10.1007/s11090-006-9003-9
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Carbon Tetrachloride Decomposition in Oxidative RF Thermal Plasma

Abstract: Decomposition of carbon tetrachloride in a RF thermal plasma reactor was investigated in oxygen-argon atmosphere. The net conversion of CCl 4 and the main products of decomposition were determined by GC-MS (Gas Chromatographic Mass Spectroscopy) analysis of the exhaust gas. Temperature and flow profiles had been determined in computer simulations and were used for concentration calculations. Concentration profiles of the species along the axis of the reactor were calculated using a newly developed chemical kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
6
0
3
Order By: Relevance
“…Therefore, it can be concluded that it is a good assumption that at thermal plasma conditions the ionic reactions have no importance compared to the neutral ones and can be neglected from the reaction mechanism without causing any significant error in the kinetic results and the product concentrations. For carbon tetrachloride thermal plasma the maximum temperature is 7,000 K. Considering a small ionization [5,12,13] the neutral concentration is far higher than the concentrations of the ions and electrons. Experimental results also prove that at atmospheric pressure in thermal plasmas the ion and electron containing reactions are slower compared to the thermal reactions, and they can be neglected from a reaction kinetic model [12,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that it is a good assumption that at thermal plasma conditions the ionic reactions have no importance compared to the neutral ones and can be neglected from the reaction mechanism without causing any significant error in the kinetic results and the product concentrations. For carbon tetrachloride thermal plasma the maximum temperature is 7,000 K. Considering a small ionization [5,12,13] the neutral concentration is far higher than the concentrations of the ions and electrons. Experimental results also prove that at atmospheric pressure in thermal plasmas the ion and electron containing reactions are slower compared to the thermal reactions, and they can be neglected from a reaction kinetic model [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…For carbon tetrachloride thermal plasma the maximum temperature is 7,000 K. Considering a small ionization [5,12,13] the neutral concentration is far higher than the concentrations of the ions and electrons. Experimental results also prove that at atmospheric pressure in thermal plasmas the ion and electron containing reactions are slower compared to the thermal reactions, and they can be neglected from a reaction kinetic model [12,13]. Orlandini and Riedel [12] investigated the NO conversion at atmospheric pressure and they found that the simulation results were in good accordance with the previous experimental results, although the ionic species were completely ignored.…”
Section: Resultsmentioning
confidence: 99%
“…Kovács et al 3,21 propuseram um modelo teórico para a decomposição do CCl 4 por pirólise em atmosfera de argônio, considerando que em temperaturas próximas a 7000 K a etapa dominante é a decomposição térmica seguindo as reações:…”
Section: Eficiência De Decomposição Do CCLunclassified
“…A adição de gases oxidantes ao plasma, por exemplo, na degradação de hidrocarbonetos reduz a formação de carbono sólido (fuligem). 3 Os oxidantes mais comuns utilizados são oxigênio ou vapor d'água, que gaseificam o carbono sólido a dióxido de carbono ou monóxido de carbono. 3 O processo de degradação por plasma térmico segue basicamente duas etapas: na primeira, a alta temperatura em conjunto com o fluxo de elétrons gerados pela ionização do gás, formando o plasma, quebra as ligações químicas das moléculas formando radicais livres e/ou íons muito instáveis que, numa segunda etapa, no esfriamento da mistura gasosa, se recombinam espontaneamente formando novas substâncias em um processo entropicamente favorável.…”
Section: Introductionunclassified
See 1 more Smart Citation